Epidemiology of pancreatic cancer in the XX and the beginning of the XXI century - A. M. Sidorenko; A. I. Shevchenko; I. S. Kugayenko (Patologìâ)
Pancreatic cancer is responsible for 227,000 deaths per year, and is the eighth most common cause of death from cancer in both sexes combined, a relative position is higher than for incidence (thirteenth) because of the very poor prognosis (the mortality / incidence ratio is 98%). Survival rates are 2% to 5% in cancer registries for the developed and developing countries. Such disappointing results of treatment are explained by early pancreatic cancer metastasis to regional lymph nodes, bone marrow and liver.